História de lutas políticas e anticomunismos: representações e disputas discursivas na imprensa alagoana (1954-1964) - Barros, Pedro Samyr de Souza (2021)
This work aims to analyze the anti-communist discourse of the Alagoas press between the years 1954 and 1964. Anti-communism has been in evidence in Brazil since the Russian revolution of 1917, however, it was developed in the 1930s and 1960s with more force in the political discourse by the propertied classes, resulting in authoritarian actions throughout the period. From a methodological point of view, we researched collections of historical institutions, in the journal sections, based on Discourse Analysis, in order to dialogue, in a more profound way, with journalistic texts and bibliographic review, in the context of the production of the analyzed newspapers (O Semeador, Gazeta de Alagoas and A Voz do Povo). These newspapers, respectively belonging to the Catholic Church, the business group led by Arnon de Melo and the Communist Party of Brazil of the Alagoas directory, were fundamental to understanding how the various circles of society in Alagoas carried out their actions according to their interests, ideologies and time historic. The choice was motivated by being a political expression of its creators, being fundamental in the construction of new approaches and problematizations. Also, by carrying part of history with them, they become true subjects of history that allows us to cast new eyes on the past. When thinking about our object, our methodologies and our sources together, we conclude that Alagoas and its social actors were inserted in the context of anti-communism and the Cold War, becoming an important chapter of Brazilian history in this context.